ANALYZE THE FACTORS THAT AFFECT CUSTOMER LOYALTY TO THE QUALITY OF THE WAITER AT ROSALIA INDAH TRANSPORT COMPANY - Yusup, Fajar Muhammad; Anastasya, Revika; Kusumastuti, Anggit Dyah (Dynamic Management Journal, 2024)
Tight competition between companies in inter-city inter-provincial bus services requires improvements in quality service to retain customers. This literature review aims to analyze the factors that influence customer loyalty towards service quality at the Rosalia Indah Transportation Company. This study examines various relevant literature to identify and understand the influence of factors such as security and safety, convenience, timeliness, customer service, and ease of ordering on customer loyalty. The results of this literature review show that all of these factors significantly influence customer loyalty, with security and safety and comfort being very influential in building customer trust and satisfaction. This study suggests that to increase customer loyalty, companies should focus on continuous improvement in these aspects of service. The findings from this literature review provide guidance for Rosalia Indah's management in strategic efforts to improve service quality and maintain customer loyalty in the transportation industry.